Nurses' Ethical Challenges During Caring for COVID-19 Patients: Literature Study - Haryati, Iis; Trisyani, Yanny; Nuraeni, Aan (Jurnal Berita Ilmu Keperawatan, 2022)
Nurses are frontliners during the COVID-19 pandemic and are vulnerable to ethical challenges when caring for patients with COVID-19. The ethical challenge of nurses is basically due to the gap between nursing practice and nursing goals. This study aims to identify empirical evidence related to the ethical challenges nurses face when caring for COVID-19 patients. This research method uses a literature study that analyzes articles from five international reputable databases such as CINAHL, Pubmed, Proquest, Science Direct, and search engines Google Scholar. The keywords used to facilitate the search for articles were 'COVID-19', 'critical care nursing', 'intensive care nursing', 'intensive care nurses', 'critical nurses', 'intensive care nurses', 'caring', 'ethical challenges', 'ethical issues', 'ethic dilemmas', ethical challenges', 'ethical issues', and 'ethical dilemmas'. with the help of boolean operators and then the articles are selected gradually using PRISMA. From the search results obtained 7 articles that deserve to be analyzed. There are three themes related to ethical challenges that occur, namely ethical challenges in the nursing care process, ethical challenges in nursing professionals, and ethical challenges in health interprofessional relationships. Ethical challenges cause nurse discomfort at work, and can even cause job stress. Regarding these results, nurses need to get support to overcome ethical dilemmas that occur through the provision of resources according to needs, preparation of SOPs regarding the roles and duties of nurses, as well as increasing knowledge regarding the care of COVID-19 patients.